Baculoviruses remodel the cytoskeleton of insect hemocytes to breach the host basal lamina - Ryuhei Kokusho; Susumu Katsuma (Communications Biology)
Abstract Many pathogens and endosymbionts hijack the host’s cytoskeleton for efficient propagation and transfer within or between host cells. Once released into the host’s circulatory system, however, they have to confront structural barriers without utilizing host cell functions. Many insect viruses and insect-borne viruses can re-enter from the hemolymph into insect tissues despite the barrier of the basal lamina (BL), but the molecular mechanism remains unclear in many cases. Here, we demonstrate that Bombyx mori nucleopolyhedrovirus (BmNPV) remodels host hemocytes to breach the BL. We found that the viral membrane protein actin rearrangement-inducing factor 1 (ARIF-1) induces filopodia-like protrusions and invadosome-like structures in hemocytes, which play a critical role in attaching to the tissue surface, penetrating the tracheal BL and thus facilitating the transport of viral nucleocapsids into host tissues. Our findings clearly show the role of hemocyte infection in viral systemic spread and its molecular basis.